AN EXPERIENCE IN USING WEB TECHNOLOGIES TO STUDY THE MNEMONIC “GOOGLE-EFFECT” - Laskov , G. D.; Bukinich, A. M. (Modern Psychology, 2019)
In this paper we present the experience of using web technologies (HTML, CSS, JavaScript) in psychological study of the mnemonic “Google-effect”. This effect consists of a tendency to forget information after the command “save” is assigned to a computer (Sparrow, Liu, Wegner, 2011). The present study explores whether the “Google-effect” would remain if the participant has an explicit mnemonic goal to remember the material. In other words, we studied how the interaction between computer operations and the participant’s goals affects the recall of the material. Seventy student volunteers (10 males) took part in the computer game requiring identifying themselves with a private detective. According to the results, the effect was not reproduced, but thanks to the capabilities of the web interface, we were able to collect additional data that allowed us to put forward an innovative interpretation of the “Google-effect”.